2009
DOI: 10.1107/s0907444909020320
|View full text |Cite
|
Sign up to set email alerts
|

Automatic implementation of precise grid screens: the four-corners method

Abstract: Example of four-corners grid mixing. Shown here are mixing proportions for the indicated grid, in a 24-well format for legibility. The proportions for the more common 96-well format are similar.short communications

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Consistent with this, several other studies have also suggested the predictive value of basal keratins on BRCA1 mutation 132 , 133 . Preclinical models of tumors with dysfunctional BRCA1 have been shown to be exclusively sensitive to cross-linking agents and inhibitors of the poly (ADP-ribose) polymerase 134 , indicating the efficient therapeutic treatment of tumors of this class.…”
Section: Hallmark 2: Activating Invasion and Metastasismentioning
confidence: 99%
“…Consistent with this, several other studies have also suggested the predictive value of basal keratins on BRCA1 mutation 132 , 133 . Preclinical models of tumors with dysfunctional BRCA1 have been shown to be exclusively sensitive to cross-linking agents and inhibitors of the poly (ADP-ribose) polymerase 134 , indicating the efficient therapeutic treatment of tumors of this class.…”
Section: Hallmark 2: Activating Invasion and Metastasismentioning
confidence: 99%
“…Crystallization plates for initial screening were prepared using the Mosquito micro volume crystallization robot at both 2:1 and 1:1 ratios of protein to precipitant with volumes of 0.1 µl:0.5 µl and 0.075 µl:0.075 µl. Optimization blocks were prepared using the Multiprobe II liquid handling robot producing 96-well grids varying precipitant concentrations using the four-corner approach to aid robotic setup (32). …”
Section: Methodsmentioning
confidence: 99%
“…The composition of the buffer systems may be altered during optimization experiments to change the pH. Obviously, all of these optimization experiments are very amenable to automation (Hennessy et al, 2009).…”
Section: Optimization Of Conditionsmentioning
confidence: 99%